Aluminium toxicokinetics after intramuscular, subcutaneous, and intravenous injection of Al citrate solution in rats - Weisser, Karin; Göen, Thomas; Oduro, Jennifer D.; Wangorsch, Gaby; Hanschmann, Kay-Martin O.; Keller-Stanislawski, Brigitte (Archives of Toxicology, 2019)
Knowledge of dose linearity, plasma clearance, rate and extent of subcutaneous (SC) and intramuscular (IM) absorption of soluble aluminium (Al) citrate is considered a prerequisite for evaluation of toxicokinetic data obtained from SC or IM administration of Al adjuvants in medicinal products. Therefore, total Al plasma kinetics was investigated after SC, IM, and IV administration of single Al doses (36 and 360 µg/kg IM or SC; 30 and 300 µg/kg IV) given as citrate solution in rats. Control groups receiving vehicle (saline) were run in parallel to monitor background plasma Al levels over time resulting from dietary intake. Evaluation of Al plasma profiles was done by both non-compartmental analysis of baseline-corrected data and simultaneous model fitting to the raw data using a population kinetics approach. High and dose-independent total plasma clearance (6.6 mL/min/kg) was observed after IV administration corresponding to 60–82% of normal rat GFR. This supports the previous assumptions that parenterally administered Al citrate is more rapidly cleared from plasma than other Al species (e.g., chloride or lactate). Furthermore, plasma exposure of Al (C max and AUC 0–inf ) increased dose-proportionally at all administration routes. Fast and complete absorption of Al was observed at each dose level after both SC and IM administration (bioavailability estimates: 88 and 110%). Estimates for the first-order absorption rate constant k a correspond to absorption half-lives of 36 min (SC) and ≤ 13 min (IM). There was no increase in tissue Al content (whole bone and brain) after 36 µg/kg IM compared to control rats.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Aluminium; Aluminium citrate; Intramuscular administration; Rat; Subcutaneous administration; Toxicokinetics